2008
DOI: 10.1093/jae/ejn025
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination of Madagascar's Vanilla Marketing Board, 10 Years on

Abstract: This paper explores how the elimination of Madagascar's Vanilla Marketing Board (VMB) in 1993 affected prices paid to farmers, incentives and indicators of poverty and inequality using household survey data and simulation analysis. Following the reforms, margins between FOB and farmgate prices have narrowed down, and the analysis of changes in poverty and inequality based on household surveys suggests a reduction in poverty and a muted supply response. A counterfactual analysis based on the observed reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…In short, the addition of those supply responses is unlikely to affect our welfare and poverty analysis. This feature of the analysis is a general result, not a property of our data (see for example Cadot et al (2009), McMillan et al (2003), Heltberg and Tarp (2002), Key et al (2000), and Lopez et al (1995)).…”
Section: Baseline Modelmentioning
confidence: 81%
“…In short, the addition of those supply responses is unlikely to affect our welfare and poverty analysis. This feature of the analysis is a general result, not a property of our data (see for example Cadot et al (2009), McMillan et al (2003), Heltberg and Tarp (2002), Key et al (2000), and Lopez et al (1995)).…”
Section: Baseline Modelmentioning
confidence: 81%
“…With this in mind, we found that regulation of the commodities trade and conservation activities in Madagascar officially remain the responsibility of the public sector, i.e., the local and national Malagasy government. This regulating role is smaller than in times past [30], as the vanilla market was a state-run monopoly prior to 1993 [77]. Today, states appear to be reasserting their regulatory power, such as in the case of forest and agricultural certification in Indonesia [78] or "land grabbing" governance [79] globally.…”
Section: Discussionmentioning
confidence: 98%
“…It is perhaps not really surprising to learn that supply responses are somewhat feeble in developing countries. The body of literature is too large for a comprehensive review, but some of most fascinating recent examples include Cadot, Dutoit, and de Melo (2009), who examined vanilla-market reforms in Madagascar, and McMillan, Welch, and Rodrik (2003), who studied cashews in Mozambique.…”
Section: Farm Supply Responsesmentioning
confidence: 99%